Screening (and creaming?) applicants to job trainings programs : the AFDC homemaker - home health aide demonstrations - Bell, Stephen H. [Verfasser]; Orr, Larry L. [Verfasser] (My University, 2002)
"Government employment and training programs typically do not have sufficient resources to serve all those who apply for assistance. Those to be served are usually selected by program staff based on management guidelines that allow considerable policy discretion at the local level. A longstanding issue in employment and training policy is whether allowing this flexibility leads to selection of applicants (1) most likely to benefit from the program or (2) who are likely to experience the highest absolute outcomes in the absence of program services, sometimes called "creaming". The distinction is crucial to the success of many programs, both as redistributional tools and as economic investments. Selection of those most likely to benefit from the program - i.e., those for whom the program's impact on subsequent labor market success will be greatest - will maximize the social return on the investment in training. In contrast, "creaming" may lead to little or no social benefit or to a substantial gain, depending on whether those selected for training - the group most likely to succeed without the tratment - in fact benefit most from it. The redistributional effects of a program will also depend on who is served: among the applicant group, a more equal distribution of economic well-being, ex post, will be achieved only if the program favors applicants likely to do worst without the intervention. This paper explores the role of creaming in the operation of seven welfare-to-work training programs, the type of programs that have been the focus of increased expenditures over the last 10 years as more and more welfare recipients have been pushed to become self-sufficient. It considers whether the program intake practices adopted in the studied programs furthered the social goals pursued and, if not, what consequences they had on the twin concerns of distributional equity and economic efficiency. The analysis begins by reviewing the history of the creaming issue and its importance in the literature. A unique data set is then examined to discover the factors that influenced admission decisions in seven state-run employment and training programs for welfare recipients and how those decisions played out in terms of the in-training performance and later labor market outcomes of program participants. The principal conclusions are that these programs "creamed" the most able applicants on both observable and unobservable characteristics, but that this targeting did not systematically affect the size program impacts or the returm on investment." (author's abstract, IAB-Doku) ((en))
Keywords: G 1.2 Arbeitsmarkt; S 2.3.2 Programme in der Berufsbildung; I 2.3.2 Nordamerika; Arbeitsmarktpolitische Maßnahme; Erfolgskontrolle; Berufliche Weiterbildung; Teilnehmer; Quantitative Angaben; USA